Persepsi Masyarakat Terhadap Kejadian Tanah Longsor Dalam Pembangunan Perumahan Mewah Kota Samarinda - Nazla Zahira Yasmin; Siti Raodah; Adhe Satryo Baratha Yuda; Aryo Mukti Nugraha; Asnawi Mubarok (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
. This research raises the issue of elite housing development on Jalan M.T. Haryono in Samarinda City, which has generated controversy due to violations and negative impacts on the surrounding. This research aims to understand the perceptions of the people of Gang 6 M. Said who became victims of landslides caused by its activities.This research uses a qualitative method with data collection techniques analyzing news articles, scientific journals, official reports, and other related documents, field observations and in-depth interviews with people in there. The results showed that the people who lived in there have almost similar perceptions towards the construction of this elite housing project. Most of the community didn’t know that the lowering of the seal of the development project had been carried out from March 2024. However, the majority of residents still feel worried after the landslide incident. Therefore, some residents moved from the area near the development project. Although, the residents also appreciate the responsibility of the housing company afterwards, starting from material responsibility and the needs such as food, blankets, and others, and thankful for the steps taken by the Samarinda City Government, which is swift to face, listen to, and follow up on this issue.